Food habits and exercise in schoolchild in the province of Granada - María Correa Rodríguez; José Antonio Gutiérrez Romero; Juan Manuel Martínez Guerrero (Fundación para el Desarrollo de la Enfermería, 2013)
Childhood obesity is a multifactorial disease that stems from the interaction of genetic and environmental or modifiable factors such as dietary habits, physical activity and the level of inactivity. We performed a cross-sectional study by applying test Kreceplus in schoolchildren aged between 11 and 12 years. 25.5% of the students did not take milk at breakfast, 34% did not eat breakfast cereals and 10.6% consumed industrial bakery products at breakfast. 42.9% of them did not eat a second daily fruit and 70.2% only eat vegetables once a day. 31.9% of children have poor nutritional level being statistically significant differences according to gender. Regarding the level of physical activity, statistically significant differences between women and men were also found, 53.2% of the school population had a regular or poor level of physical activity and 66% spend 2 or more hours per day in sedentary activities. Data obtained show unhealthy eating habits and increased inactivity rates among the school population studied. The study enKid, Avall and others show very similar trends. This study provides a baseline for future intervention programs for the prevention of obesity and overweight in children, based on the importance of proper eating habits and physical exercise.